RELIGIOUS BASED MANAGEMENT (Religiosity as the Basis for Developing Salafi Education Curriculum Management in East Lombok) - Mashun (TADBIRUNA: Jurnal Manajemen Pendidikan Islam, 2026)
This article will discuss the role of religion as a basis for curriculum development in Salafi education in East Lombok. This research uses qualitative methods with a field research approach . Data collection techniques include participant observation, structured interviews, and documentation. The data analysis stages refer to the procedures of Milles and Haberman. The results of this research show that firstly it is based on spiritual values based on the Al-Quran and Hadith, as the foundation of the curriculum it emphasizes aqidah, shari'ah and morals based on As-Sunnah values, as a guide to learning methods by applying the talaqqi and musyafahah, halaqah, exemplary, tahfiz, muhadatsah methods, as learning evaluation assessments are carried out through oral exams, book exams, observation of morals and behavior, as well as reports on the development of worship. Secondly, maintaining the purity of the teachings of As-Sunnah by upholding correct justification according to the Qur'an and As-Sunnah and rejecting practices which are categorized as bid'ah or practices which are not based on clear evidence, forming an Islamic personality through dormitory activities, book learning, tahfîdz programs, the habit of carrying out the Sunnah, and social activities of da'wah, as well as becoming a Mujahideen army. The third requirement for students is to conduct an initial assessment of each student, arrange tiered classes for tahfis, provide special guidance programs for students who are late in understanding, provide enrichment materials, and implement the Islamic Boarding School curriculum as a distinctive feature